Understanding the impact of delayed diagnosis and misdiagnosis of systemic lupus erythematosus (SLE) - Jordan L. Mitchell (Journal of Family Medicine and Primary Care)
Systemic lupus erythematosus (SLE) is a complex and multifaceted autoimmune disease that poses a significant diagnostic challenge for healthcare providers due to its diverse clinical manifestations, lack of specific testing, and potential to mimic other conditions. Delayed diagnosis and misdiagnosis of SLE can have serious consequences for patients, impacting their physical and psychological well-being. The physical consequences of delayed diagnosis and misdiagnosis of SLE are significant. Studies have shown that delays in diagnosis can lead to increased organ damage, poorer health outcomes, and increased morbidity and mortality. With a delayed diagnosis or misdiagnosis, patients may also experience increased psychological symptoms, such as depression, anxiety, and lack of trust in clinicians. The median delay from the first symptom to diagnosis in SLE is 47 months, highlighting the need for early recognition and management. Delayed diagnosis can lead to increased disease progression, which can result in irreversible organ damage and long-term complications. This paper investigates the multifaceted consequences of delayed diagnosis and misdiagnosis of SLE, encompassing both physical and psychological impacts. It delves into the underlying reasons behind diagnostic delays and offers comprehensive strategies for healthcare providers to enhance early recognition and management. Through a thorough analysis of medical literature and statistical data, this paper aims to provide physicians with actionable insights to improve diagnostic accuracy and patient outcomes in SLE.